A NEW METHOD FOR CALCULATION OF FUZZY RESPONSE SPECTRA OF EARTHQUAKE MOTION IN LOWLAND - Ansari A.; Noorzad A. (Lowland Technology International, 2004)
The characteristic parameters of a system which are involved in dynamic analysis of a structure i.e. mass, stiffness and damping in addition to the input excitation have got some kind of fuzziness and vagueness. This vagueness is due to imprecise determination of such paraemeters and the complexity of real dynamic systems which are common in lowlands. On the other hand, nonhomogenity in soil properties and complex topography of soil layers have a great influence on the response of the ground. As a result, the effect of uncertainty of these parameters on the ground response is very important. This kind of uncertainty is not like randomness and it is necessary to consider it with the help of Fuzzy mathematics. In this paper a new method for fuzzy dynamic analysis of systems is introduced. According to this model, by the means of the a prallel system, the problem of combination explosion, which is due to fuzziness of system parameters, is solved. Moreover, the results of a study on the influence of different parameters’ fuzziness on the response spectrum are presented and a comparison between results of fuzzy analysis and traditional sensitivity analysis is made. Meanwhile, the effects of such uncertainty on response spectra are described.